The Wiley 5G REF - Tafazolli, Rahim; Wang, Chin-Liang; Chatzimisios, Periklis; Liyanage, Madhusanka (New Jersey: Wiley Data and Cybersecurity, 2021)
"From the Section Editor's Foreword by Dr. Madhusanka Liyanage, University College Dublin, Ireland. The Wiley 5G Ref: Security offers a stellar collection of articles selected from the online-only work, The Wiley 5G Reference. It aims to provide a solid educational foundation for researchers and practitioners in the field of 5G Security and Privacy to expand their knowledge base by including the latest developments in these disciplines. The book introduces the security landscape of 5G, and significant security and privacy risks associated with the 5G networks. Then, the security solutions for different segments of the 5G network, i.e., radio network, edge network, access network, and core network, are discussed. Since 5G is developed based on network softwarization, security threats associated with key network softwarization technologies such as SDN, NFV, NS, and MEC are also presented in detail. Then, the security issues related to the new 5G and IoT services are delivered. Finally, a detailed discussion on the privacy of 5G networks is presented by considering Datafied Society. Written by leading experts in security and privacy for the telecommunication network, this book is intended to provide additional learning opportunities for a wide range of readers, from graduate-level students to seasoned engineering professionals. We are confident that this book and the entire collection of selected articles will continue Wiley's tradition of excellence in technical publishing and provide a lasting and positive contribution to the teaching and practice of security and privacy of 5G and beyond networks"--
Keywords: 5G mobile communication systems -- Security measures